Alluvial - Fluvial Architecture of Synrift Deposits: An Observation from the Outcrops of Brani Fm., Ombilin Basin, West Sumatra - Ari Wibowo; Iqbal Fardiansyah (Berita Sedimentologi, 2016)
Synrift sediments are currently a major focus of both academic research and industrial interest related to petroleum exploration, particularly with regard to their reservoir potential. Reservoirs are alluvial - fluvial deposits with a variety of sedimentary architectures. Their complexity requires good knowledge of basic sedimentology and use of outcrop analogies. The Brani Fm. of the Ombilin Basin has good outcrops that can be used as surface geology model. This paper uses measured outcrop data from the synrift, alluvial - fluvial sediments to characterize reservoirs, revealing that reservoir properties, such as porosities and permeabilities have wide ranges. Thicker sand body geometries in channel assemblages have good connectivity. Utilizing outcrop data is a useful analogue for the surrounding subsurface to tie into the geophysical data.